2007
DOI: 10.1002/mar.20188
|View full text |Cite
|
Sign up to set email alerts
|

Gratitude, delight, or guilt: The role of consumers' emotions in predicting postconsumption behaviors

Abstract: This study investigates the relationships among appraisals (goal congruence/incongruence and agency), consumption emotions (gratitude, happiness, guilt, anger, pride, and sadness), and postconsumption behaviors (positive and negative word of mouth, repurchase intention, and complaint behavior). The findings demonstrate that these emotions predict different specific types of post-consumption behaviors and that they are elicited by appraisals specified in the psychology literature. In particular, gratitude but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
263
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(277 citation statements)
references
References 54 publications
(89 reference statements)
9
263
0
5
Order By: Relevance
“…Second, predicating upon the theory of social sharing, this study was amongst the first to show empirically that openly expressed emotions significantly and directly precede negative O-WOM. By demonstrating that both positive and negative affect play a substantial role in the distribution of negative O-WOM our research extends prior research proposing negative emotion as primary WOM determinant (Babin & Babin, 2001;Machleit & Eroglu, 2000;Soscia, 2007 …”
Section: Theoretical Implicationssupporting
confidence: 83%
“…Second, predicating upon the theory of social sharing, this study was amongst the first to show empirically that openly expressed emotions significantly and directly precede negative O-WOM. By demonstrating that both positive and negative affect play a substantial role in the distribution of negative O-WOM our research extends prior research proposing negative emotion as primary WOM determinant (Babin & Babin, 2001;Machleit & Eroglu, 2000;Soscia, 2007 …”
Section: Theoretical Implicationssupporting
confidence: 83%
“…Bock et al (2016) identify the importance of supportive employee-customer interactions as facilitators of gratitude's positive impact on relational behaviours. In the consumer context, scholars have discovered that gratitude is a driver of purchase intention (Palmatier et al 2009;Soscia 2007;Simon et al 2015;Dewani et al 2016), sales growth (Palmatier et al 2009), loyalty (Bock et al 2015;Dewani et al 2016), positive wordof-mouth communication (Raggio et al 2014;Soscia 2007) and willingness to pay (Morales 2005). Whilst only positive word-of-mouth may be appropriate in the context of media-practice education, the range of outcomes indicates the potential power of gratitude.…”
Section: Gratitude and Relational Exchanges: Drivers And Outcomesmentioning
confidence: 99%
“…Recently, research in the area of guilt seems to have increased somewhat. For example, guilt has been studied in the context of consumption emotions and postconsumption behaviors (Soscia, 2007). With regard to the charitable donation context specifically, Basil, Ridgway, and Basil (2006) have shown that the impact of guilt on charitable donations hinges on a feeling of responsibility.…”
Section: Literature Reviewmentioning
confidence: 99%